Mapeamento de plantas daninhas em diferentes coberturas de solo na cultura da soja - Fistarol, Caroline (2021)
The incidence of weeds is one of the main problems faced in soybean cultivation. Thus, in order to identify which, cover plant causes greater suppression in the emergence of these invaders, an experiment was conducted in the annual crop teaching and research unit of the Federal Technological University of Paraná, campus of Dois Vizinhos. The experimental delimitation to be used is of random blocks, with four treatments and three repetitions: T1 brachiaria (Brachiaria decumbens), T2 millet (Pennisetum glaucum), T3 lablab (Lablab purpureus) and T4 crotalaria (Crotalaria juncea). However, with the advance of technology and precision agriculture the use of unmanned aerial vehicles (UAV) was an alternative for identifying which covering plant among the seed bank provide greater supression. Thus, it is intended to map and evaluate through images obtained using RGB cameras mounted on UAV's the percentage of weeds supressed over determined phenologicalstages of soybean cultivation.The photointerpretation method and conventional weed counting were added, indicating that less weed occurred in T1. Comparing the identification methods (conventional to field and photointerpretation) it was found that there was no difference between the means of evaluation. Weed distribution maps have been generated, which will help in their management.